2020
DOI: 10.3390/app10041492
|View full text |Cite
|
Sign up to set email alerts
|

Academic Success Assessment through Version Control Systems

Abstract: Version control systems’ usage is a highly demanded skill in information and communication technology professionals. Thus, their usage should be encouraged by educational institutions. This work demonstrates that it is possible to assess if a student can pass a computer science-related subject by monitoring its interaction with a version control system. This paper proposes a methodology that compares the performance of several machine learning models so as to select the appropriate predicting model for the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Neural network [15,18,19,24] No retraining is required because it learns events; it is applicable to real-world issues, and there are few parameters to alter, making it simple to use.…”
mentioning
confidence: 99%
“…Neural network [15,18,19,24] No retraining is required because it learns events; it is applicable to real-world issues, and there are few parameters to alter, making it simple to use.…”
mentioning
confidence: 99%
“…In addition, MoEv cleans data and performs other preprocessing operations. It was successfully used in different research areas such as jamming-attack detection in real-time location systems [ 21 ], or academic-success prediction at educational institutions [ 22 ]. However, it has not been validated on malicious-network-traffic detection yet.…”
Section: Discussionmentioning
confidence: 99%
“…ey found that the time-dependent variables significantly impact the online learning performance. In several programming-related courses, Guerrero-Higueras et al [13] use the submission records in the version control system to monitor students' work progress to evaluate their academic performance and predict whether they will pass the course. Likewise, Wang et al [14] feed students' program submission sequence into a recurrent neural network (RNN) model to obtain representations of the student's knowledge and then predict their future performance.…”
Section: Related Workmentioning
confidence: 99%
“…e loss value of each batch can be computed by ( 13) and (14). First, the softmax operation, defined as (13), is performed to scale the instance's outputs to value range [0, 1] and the sum to 1, where y i represents the probability of the instance belonging to the ith category, x i is the ith output of the input instance, K is the total number of the instance outputs (equal to the number of categories of the instances), and the category number here is two. en, the binary cross-entropy loss, defined as (14), is calculated, where y i is the ground truth category of instance i, and 􏽢 y i is the predicted probability of instance i belonging to the ground truth category.…”
Section: Experimental Settingsmentioning
confidence: 99%